Investigation on the Background Radiation of Abakaliki Rice Mill in Ebonyi State, Nigeria - A. Nwachukwu; F. C. Ikeagwuani; A. O. Adeboje (Atom Indonesia, 2021)
This study investigated the background ionizing radiation of Abakaliki rice mills. The requirement to monitor this site is because the prevalent activities in the site suggest that it is a source of ionizing radiation. The activities include fuel stations and excavation sites. Other sources are various chemicals and agrochemicals (like Phosphate, Uranium, Thorium, and Radium) used during the planting of the different rice species. There is, therefore, an urgent need to investigate the radiation level of Abakaliki rice mills in Ebonyi state, Nigeria to ascertain if it has passed the safety standards. The investigation was carried out using the Radalert 100 radiation monitor and a geographical positioning system (Garmin GPSMAP 765). The studied site was split into different points with each representing a mill that houses different grinding plants. This study included all the sections of the mill. The mean background radiation exposure rate ranges from 0.014mRhr-1to 0.0204mRhr-1. The obtained values are higher than the world standard limit of 0.013mRhr-1 recommended by ICRP except point 7 which corresponds to the top of the rice husk dumpsite. The calculated absorbed dose rates for the various sections of the mill ranged from 99.18 nGh-1 to 177.48 nGyh-1. These values of absorbed dose rates were observed to be far higher than the world permissible value of 89 nGyh-1. The annual effective dose equivalent (AEDE) for the exposure values ranged from 0.122 mSvy-1 to 0.218 mSvy-1 which are far lower than the ICRP permissible limits of 1.00 mSvlyr for the public and therefore implies absence of any immediate radiological risk. The excess lifetime cancer risk for the mill users were all above the 0.29 × 10-3 world recommended value. This suggests a possibility of the rice mill workers developing radiation-related illnesses over time.